Head-On Dynamic Manifestations in the Roadway Driving with Small Coal Pillar under the Influence of Roof Drainage: A Case Study from Uxin Banner. (23rd August 2022) - Cheng, Yunhai; Li, Fenghui; Zhang, Xiufeng; Wang, Chao; Li, Gangwei
Abstract : In the Uxin Banner area of the Inner Mongolia Autonomous Region, mines that have experienced rock bursts have all been affected by the presence of confined water in the roof strata. Strong mine pressure appears in the working face with about 30 m wide coal pillar in this area, and the research and practice of prevention and control of rock burst by small coal pillar are carried out. Mining-related events linked to the preservation of small coal pillars in the 2-2 coal seam of this region, and studies of the phenomenon, have shown that head-on rock bursts occur during gob-side roadway driving at the edge of the drained area, making it necessary to identify the sources of pressure triggering the events, to determine the related threshold criteria, and to identify methods to reduce the occurrence and magnitude of the rock burst events. This study used the gob-side entry driving in the drained area of the 2202 auxiliary haulage roadway of a mine as a case study. The paper built a structural and computational model for overburdens (including the drained stratum) before mining disturbance, based on the theory for a continuously distributed Winkler elastic foundation. The models used and developed in our study were used to identify, quantify, and describe the changes to stress and the transfer of stress during the drainage process. On the basis of the effects of drainage stress induced by the gob-side entry driving, we outlined a method for ranking the level of rock burst hazard associated with the areas in and adjacent to the drained area. The level of rock burst hazard associated with the entry driving could be arranged in descending order as follows: parallel boundary > vertical boundary > undrained area > drained area. Stress threshold criteria for head-on ejection were also proposed in the paper, namely, (1) the occurrence (or not) of coal ejection during loading and (2) the critical stress for the occurrence of ejection. Field monitoring indicated that microseismic events and energy are mainly concentrated in the driving region parallel to the boundary of the drained area. We concluded that head-on large-diameter borehole destressing would effectively reduce the likelihood of a rock burst occurrence.